1998
DOI: 10.1152/ajplung.1998.274.5.l762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anion secretion inhibitors on mucin content of airway submucosal gland ducts

Abstract: In porcine bronchi, inhibition of both Cl− and[Formula: see text] transport is required to block the anion secretion response to ACh and to cause mucus accumulation within ACh-treated submucosal gland ducts [S. K. Inglis, M. R. Corboz, A. E. Taylor, and S. T. Ballard. Am. J. Physiol. 272 ( Lung Cell. Mol. Physiol. 16): L372–L377, 1997]. In this previous study, a combination of three potential [Formula: see text] transport inhibitors [1 mM acetazolamide, 1 mM DIDS, and 0.1 mM dimethylamiloride (DMA)] was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
71
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 14 publications
9
71
1
Order By: Relevance
“…Fluid secretion by pig airway glands is driven by anion secretion (10,(30)(31)(32)(33)(34), and the lack of synergy in tissues from humans with CF indicated that synergy in humans requires CFTR. We next sought to determine the relative contributions of CFTR and Ca 2+ -activated chloride channels to the synergistic effect in pig glands.…”
Section: Dose-response Relations For Single Gland Mucus Secretion In mentioning
confidence: 99%
“…Fluid secretion by pig airway glands is driven by anion secretion (10,(30)(31)(32)(33)(34), and the lack of synergy in tissues from humans with CF indicated that synergy in humans requires CFTR. We next sought to determine the relative contributions of CFTR and Ca 2+ -activated chloride channels to the synergistic effect in pig glands.…”
Section: Dose-response Relations For Single Gland Mucus Secretion In mentioning
confidence: 99%
“…Gland secretion in response to pharmacological mediators has been extensively studied in the tracheas and isolated airways of pigs Inglis, Corboz et al 1998;Trout, Gatzy et al 1998;Trout, King et al 1998;Ballard, Trout et al 1999;Crews, Taylor et al 2001;Trout, Corboz et al 2001;Phillips, Hey et al 2003;Trout, Townsley et al 2003;Ballard and Inglis 2004;Ballard, Trout et al 2006). Control experiments establish that secretions studied in this way are virtually all from the submucosal glands.…”
Section: Airway Submucosal Glandsmentioning
confidence: 99%
“…Optimal ciliary function is favoured by an alkaline rather than an acidic environment [12]. Additionally, mucin solubility is enhanced by a high pH [15] and inhibition of bicarbonate secretion has been shown in an animal model to result in total occlusion of the submucosal glands by mucin [14]. Such occlusion, with associated glandular hypertrophy, is one of the first signs of lung pathology in newborn children with CF [16], although this has not been a consistent finding in all studies [17].…”
mentioning
confidence: 99%
“…CFTR mutations could thus alter ASL pH which in turn could alter a number of innate defence processes. For example, both ciliary function [12,13] and mucus viscosity have been shown to be pH dependent [14]. Optimal ciliary function is favoured by an alkaline rather than an acidic environment [12].…”
mentioning
confidence: 99%